PERLINDUNGAN HUKUM TERHADAP KORBAN PENYALAHGUNA NARKOTIKA DENGAN BERLAKUNYA UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - A.A. Istri Mas Candra Dewi (University of Udayana, 2012)
This Study in the legal protection of the victims of narcotics abusers aims todecrypt and analyze aspects of issues related to the concepts that underlie theneed for justification of legal protection of the victims and supervision of theimplementation of the decisions of rehabilitation, as well as decrypt and analyzethe legal form of protection. This study is a normative one using law approachand legal concept analysis. The results of the study indicate the legal protection ofvictims of drug abusers can not be detached from the underlying idea of legalprotection of the victims of narcotics abusers in the form rehabilitasi. Legalprovisions governing the rehabilitation of drug addicts measures stipulated inArticle 54, 56.103, and was associated with article 127 of Law No. 35 of 2009,SEMA No. 4 of 2010 as The Guideline on the implementation of the rehabilitationof narcotics abusers, but monitoring of the rehabilitation measures notaccommodated in such provisions so that there are gaps in the law enforcementmechanism of action monitoring narotics rehabilitation.